Dandelion‐Like Tailorable Nanoparticles for Tumor Microenvironment Modulation. Issue 21 (12th September 2019) - Guo, Qin; He, Xi; Li, Chao; He, Yongqing; Peng, Yiying; Zhang, Yu; Lu, Yifei; Chen, Xinli; Zhang, Yujie; Chen, Qinjun; Sun, Tao; Jiang, Chen
Abstract: Tumor‐associated macrophages (TAMs) constitute over 50% of the number of cells within the tumor, playing a major role in tumor progression and invasion. Remodeling the tumor immune microenvironment by modulating TAM polarization has been emerging as a new and promising therapeutic strategy. However, the high interstitial fluid pressure and dense extracellular matrix lead to insufficient penetration of nanosized therapies. To overcome this dilemma, an acid‐triggered size‐changeable nanoparticle (aptamer/acid sensitive linker crosslinked DGL/zoledronic acid, i.e., Apt@(DGL‐ZA) n NPs) with effective tumor distribution, extravasation, and penetration is designed. Dendrigraft poly‐ L ‐lysines (DGLs) which can induce tumor autophagy as mimics of natural abnormal proteins are crosslinked via a mild‐acid‐responsive linker (1, 6‐bis(4‐formylbenzoyloxy) hexane). Long circulation property and tumor penetration are achieved simultaneously by catching DGLs in neutral pH while releasing them in the tumor's pH, like dandelion seeds in midair. The macrophage conditioning agent zoledronic acid (ZA) is loaded on DGLs by the charge attraction. A Tenascin‐C targeting aptamer (GBI‐10) is modified onto (DGL‐ZA) n NPs for a tumor‐homing effect. Apt@(DGL‐ZA) n NPs show both enhanced penetration in in vitro 3D triple negative breast cancer spheroids and in vivo tumor tissues. Effective macrophage regulation, enhanced tumor autophagy, and excellent in vivo antitumor efficacy are achieved, suggesting this tactic as a significant antitumor strategy. Abstract : Remodeling the tumor immune microenvironment via modulation of tumor‐associated macrophage polarization is an effective strategy for tumor therapy, but limited by the high interstitial fluid pressure and dense extracellular matrix. A novel type of pH triggered Apt@(DGL‐ZA) n nanoparticles is developed for enhanced tumor penetration and deep macrophage polarization in vivo.